Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1080/03014460600882561
|View full text |Cite
|
Sign up to set email alerts
|

Genetic ancestries in northwest Cambodia

Abstract: A survey of the genetic ancestry of 125 Cambodian children resident in Siem Reap province was undertaken, based on eight Y-chromosome binary polymorphisms and sequencing of the mtDNA HV1 region. The data indicated a largely East Asian paternal ancestry and a local Southeast Asian maternal ancestry. The presence of Y-chromosomes P* and R1al* was suggestive of a small but significant Indo-European male ancestral component, which probably reflects the history of Indian, and later European, influences on Cambodia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…Since we do not find any root lineage of M31a1 or M32 in Myanmar populations, suggesting Myanmar unlikely being the source place of haplogroup M31 or M32. After re-analyzing additional 4180 mtDNAs from East Asia (Qian et al, 2001;Wen et al, 2004;Li et al, 2007;Gan et al, 2008;Zhao et al, 2009), mainland Southeast Asia (Black et al, 2006;Li et al, 2007;Irwin et al, 2008;Lertrit et al, 2008;Zimmermann et al, 2009;Peng et al, 2010) and Island Southeast Asia (Tajima et al, 2004;Hill et al, 2006Hill et al, , 2007, we did not observe any M31 or M32 mtDNA either, again substantiating our observation.…”
Section: Resultssupporting
confidence: 90%
“…Since we do not find any root lineage of M31a1 or M32 in Myanmar populations, suggesting Myanmar unlikely being the source place of haplogroup M31 or M32. After re-analyzing additional 4180 mtDNAs from East Asia (Qian et al, 2001;Wen et al, 2004;Li et al, 2007;Gan et al, 2008;Zhao et al, 2009), mainland Southeast Asia (Black et al, 2006;Li et al, 2007;Irwin et al, 2008;Lertrit et al, 2008;Zimmermann et al, 2009;Peng et al, 2010) and Island Southeast Asia (Tajima et al, 2004;Hill et al, 2006Hill et al, , 2007, we did not observe any M31 or M32 mtDNA either, again substantiating our observation.…”
Section: Resultssupporting
confidence: 90%
“…Coalescence times of mtDNA haplogroups of interest were calculated by ρ statistic method [28]–[29] using recently corrected calibrated mutation rate: 18,845 years per mutation in HVS-I (16090–16365) [30]. Reference population data on the Y chromosomes [14], [18], [31][44] and mtDNA [8][10], [45][69] were retrieved from the literature. Time estimations for main Y chromosomal lineages were made using 15 STRs (excluding DYS385a and DYS385b) in BATWING [70] under a model of exponential growth from an initially constant-sized population.…”
Section: Methodsmentioning
confidence: 99%
“…Studies of mtDNA diversity have shown that the AA speakers from Southeast Asia and the Indian subcontinent carry mtDNAs of different sources [7,9,14,16,29,30]. Although the data on Southeast Asian populations, which speak languages of the Mon-Khmer branch of the AA tree, are still somewhat limited, it seems safe to conclude, that their mtDNA characteristics are similar to those of the surrounding Southeast Asian populations, and distinct from AA tribes of India (Munda-speakers) [30]. Similarly, the Indian tribes speaking different Munda languages show generally the same mtDNA haplogroup composition as the Indo European and Dravidic groups of India [9,14,16,29].…”
Section: Introductionmentioning
confidence: 99%